DESIGNING A FLEXIBLE COMPANY ORGANIZATION MODEL IN DYNAMIC BUSINESS CONDITIONS - Marković, Snežana; Carić, Marko; Đaković, Vladimir (Ekonomija - teorija i praksa, 2022)
The subject of research in this paper is the design of a flexible model of organizational structure in dynamic business conditions. Accordingly, the focus of the research is on analyzing the impact of turbulent environment on the strategic behavior of the company and redesigning the organizational structure as well as changes related to the financial policies of the company. The aim of this paper is to determine how companies in transition, with the redesign of their organizational structure, and redesign of financial policy of the company can accelerate the transformation process, and through business rationalization, to reduce costs and increase efficiency. The main results of the research indicate that in order to achieve the above goal, companies should essentially combine mechanical and organic design in order to ensure the stability and dynamism of the model, i.e. to achieve both efficiency and effectiveness.